Application of an Arbitrary Lagrangian-Eulerian Method to Modelling the Machining of Rigid Polyurethane Foam - Horak, Zdenek; Tichy, Petr; Dvorak, Karel; Vilimek, Miloslav (Materials (Basel, Switzerland), 2021)
Rigid polyurethane (PUR) foam, which has an extensive range of construction, engineering, and healthcare applications, is commonly used in technical practice. PUR foam is a brittle material, and its mechanical material properties are strongly dependent on temperature and strain rate. Our work aimed to create a robust FE model enabling the simulation of PUR foam machining and verify the results of FE simulations using the experiments' results. We created a complex FE model using the Arbitrary Lagrangian-Eulerian (ALE) method. In the developed FE model, a constitutive material model was used in which the dependence of the strain rate, damage initiation, damage propagation, and plastic deformation on temperature was implemented. To verify the FE analyses' results with experimentally measured data, we measured the maximum temperature during PUR foam drilling with different densities (10, 25, and 40 PCF) and at various cutting speeds. The FE models with a constant cutting speed of 500 mm/s and various PUR foam densities led to slightly higher Tmax values, where the differences were 13.1% (10 PCF), 7.0% (25 PCF), and 10.0% (40 PCF). The same situation was observed for the simulation results related to various cutting speeds at a constant PUR foam density of 40 PCF, where the differences were 25.3% (133 mm/s), 10.1% (500 mm/s), and 15.5% (833 mm/s). The presented results show that the ALE method provides a good match with the experimental data and can be used for accurate simulation of rigid PUR foam machining.
Keywords: PUR foam; Arbitrary Lagrangian Eulerian; machining; finite element (FE) analyses